Stabilisation/solidification of zinc- and copper-contaminated soils using cementitious binders - Lim, Thiam Loong (2018)
This report presents detailed studies on the engineering properties and the leaching behaviour, along with the microstructural characteristics of a zinc (Zn)-contaminated soil stabilised with cementitious binders including magnesium oxide (MgO), calcium oxide (CaO) and Portland cement. Specimens are prepared by adding different concentrations of Zn chloride (ZnCl2) into the soil as contaminants at different levels of Zn concentrations. The Zn concentrations added into the specimens are predetermined at 0.2%, 0.4%, 0.8%, 1.6% and 3.2%. The specimens are compacted and cured for 28 days before tests are carried out to determine properties such as density, water content, unconfined compressive strength (UCS). In addition, leaching test and X-ray diffraction (XRD) analysis are conducted to evaluate the effectiveness of different binders in the implementation of stabilisation/solidification (S/S) technique on Zn-contaminated soil.